5ln(x-11)-3=7

Simple and best practice solution for 5ln(x-11)-3=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5ln(x-11)-3=7 equation:


Simplifying
5ln(x + -11) + -3 = 7

Reorder the terms:
5ln(-11 + x) + -3 = 7
(-11 * 5ln + x * 5ln) + -3 = 7
(-55ln + 5lnx) + -3 = 7

Reorder the terms:
-3 + -55ln + 5lnx = 7

Solving
-3 + -55ln + 5lnx = 7

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + -55ln + 3 + 5lnx = 7 + 3

Reorder the terms:
-3 + 3 + -55ln + 5lnx = 7 + 3

Combine like terms: -3 + 3 = 0
0 + -55ln + 5lnx = 7 + 3
-55ln + 5lnx = 7 + 3

Combine like terms: 7 + 3 = 10
-55ln + 5lnx = 10

Reorder the terms:
-10 + -55ln + 5lnx = 10 + -10

Combine like terms: 10 + -10 = 0
-10 + -55ln + 5lnx = 0

Factor out the Greatest Common Factor (GCF), '5'.
5(-2 + -11ln + lnx) = 0

Ignore the factor 5.

Subproblem 1

Set the factor '(-2 + -11ln + lnx)' equal to zero and attempt to solve: Simplifying -2 + -11ln + lnx = 0 Solving -2 + -11ln + lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -11ln + 2 + lnx = 0 + 2 Reorder the terms: -2 + 2 + -11ln + lnx = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -11ln + lnx = 0 + 2 -11ln + lnx = 0 + 2 Combine like terms: 0 + 2 = 2 -11ln + lnx = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 8x^2-6x-3=0 | | 3(5-15)=m-5 | | 3x+25=12x+83 | | 3a-1(-1)=-5 | | 4(3y-3)-2y=-9 | | 4v+-3v-4=13 | | 6x^2-2x^3-4x=0 | | 2k-16-10k=-2k | | 207-7x=38x+22 | | -12-3+9= | | 6(x+4)-(2x-8)= | | 5-(-8)=x | | y^2-5y-3=0 | | 5(d-6)+6= | | 2m^3-5m^2-12m=0 | | (2x-3)+(x^2-4x)=180 | | 5x^2+3x-16=32-31x | | -3u+8=14 | | c-(-2)=68 | | 3y+4=-20 | | 56=4y | | 50=(x+10)x | | [(5*6-4)-20]= | | 2a+10=26 | | c+-52=68 | | x-9.51=2.4 | | -2b+8=-8 | | 241=5(5-7x)+8x | | 3c+5=-13 | | -5+(8-14)-(-4-9)= | | 17=3(p-4)+8 | | 10n-15=85 |

Equations solver categories